2015
DOI: 10.1016/j.aninu.2015.06.001
|View full text |Cite
|
Sign up to set email alerts
|

Effects of feed form and feed particle size on growth performance, carcass characteristics and digestive tract development of broilers

Abstract: This study was conducted to evaluate the effects of feed form (mash and crumble-pellet) and feed particle size (fine, medium and coarse) on growth performance, carcass characteristics and digestive tract development of broilers. A total of 1,152 one day-old Ross 308 mixed-sex broilers were used in a factorial arrangement (2 × 3) based on a completely randomized design with six replicates of 32 birds each. Higher average daily gain (ADG) and average daily feed intake (ADFI) were observed (P < 0.01) for birds fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
23
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(40 citation statements)
references
References 18 publications
6
23
1
Order By: Relevance
“…Jahan et al (2006) reported that crumble form of feed is better than mash and pellet form for the production of the commercial broiler for the age duration of 21 to 56 days. These results were confirmed by Ommati et al (2013) and Lv et al (2015). On the other hand, Lal and Atapattu (2007) and Ahmed and Abbas (2012) concluded that the growth traits of broiler did not affect significantly by the inclusion of different forms of diets.…”
supporting
confidence: 79%
See 1 more Smart Citation
“…Jahan et al (2006) reported that crumble form of feed is better than mash and pellet form for the production of the commercial broiler for the age duration of 21 to 56 days. These results were confirmed by Ommati et al (2013) and Lv et al (2015). On the other hand, Lal and Atapattu (2007) and Ahmed and Abbas (2012) concluded that the growth traits of broiler did not affect significantly by the inclusion of different forms of diets.…”
supporting
confidence: 79%
“…April 2016 | Volume 4 | Issue 2 | Page 34 several researchers (Amerah et al, 2007;Zang et al, 2009;Dozier et al, 2010;Zohair et al, 2012;Lv et al, 2015). The advantage of crumble and pellet may result from an increase in appetite and diet density and a decrease in feed waste ( Jensen, 2000).…”
Section: Journal Of Animal Health and Productionmentioning
confidence: 99%
“…As the primary feed form for poultry rearing, pellets have been used extensively in the world [3][4][5] . Compared with the mash feeds, pelleted animal feeds have the following advantages: more consistent size and higher bulk density, better flow property and thus improved ease of handling and transportation, decreased ingredient segregation and less dust formation during processing and thus less feed wastage, improved palatability and animal performance [4][5][6][7][8] . However, there are several problems with pelleted animal feeds, including high energy consumption and unstable product quality during the feed pelletization process.…”
Section: Introduction mentioning
confidence: 99%
“…Feeds without antibiotics are increasingly used in poultry nutrition to improve growth performance and meat quality. Consequently, this has led to adaptation in At present, pelleting of feed is the most common processing method employed by feed manufacturers to improve animal performance and meat quality (Lv et al, 2015). Also, according to several reports, pelleted diets in broiler increased body weight and improved feed conversion compared to mash feeds (Amerah, Ravindran, Lentle, & Thomas, 2008;Chewning, Stark, & Brake, 2012).…”
Section: Introductionmentioning
confidence: 99%